Health-service utilization by pregnant women in the greater Mafikeng- Mmabatho district - C.F. Pretorius; M. Greeff (AOSIS, 2004)
Since the implementation of free maternity services in South Africa from 1994, more maternity services were provided (SA, 1994: 73). These services are however inaccessible to many pregnant women in the rural areas, leading to sub-optimal antenatal health service utilization. Another problem that emerged, is deterioration in antenatal health service rendering throughout the country, as well as a lack of guidelines for the mobilization of pregnant women in order to promote optimal antenatal health service utilization (ANHSU) in the North West Province. The mentioned problems were the reasons for undertaking this research.